(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Education and training aims to provide an opportunity to improve the skills and personnel in their skills, especially in areas related to leadership or managerial required in the achievement of the objectives of the organization. In fact the structural Training is not given to most of the ASN in Bitung city areas Secretariat, thus causing some structural position of Echelon III and IV Echelon structural position still held by the ASN which has yet to meet the requirements of appropriate structural level Training position. These conditions can cause structural officials leadership competencies to be weak or insufficient. Based on the issue of the purpose of this research is to find out and measure the influence of the education and training of leadership competencies to increased structural apparatus of the civil State in the Secretariat of the Regional City of Bitung. This research is exploratory research method. This usage of the intent to address education and training Are a structural effect on the competence of the leadership of the Civil State Apparatus in Bitung city areas Secretariatâ€ The results showed significant relationships had a structural Training against the leadership competencies ASN in the Secretariat City of Bitung. It is seen from the value of the correlation R = 0.86 turns approaching the maximum value of the correlation coefficient (1.00), and the value of the coefficient of determination (R-square) of 0.74 has significance that the development/enhancement of leadership competence ASN in Bitung City Area is the Secretariat of 74 or 0.74% determined/ influenced by variable structural Training, while the rest amounted to 26% specified/ influenced by other variables. This means that the higher the structural Training undertaken/ gained ASN then the higher leadership competencies from the ASN concerned. Structural determination of power have training/ significant deciding against the leadership competencies ASN in the Secretariat City of Bitung. This means that the level of competence of the leadership of the ASN is significantly influenced by structural Training followed/retrieved. Training structural influence on attitudes and behavior of the ASN in carrying out the duties of their Office. Keywords: education and training, structural, competence, leadership, Civil State Apparatus (ASN)